Entrepreneurial orientation as a growth strategy in the South African engineering sector - Ruis, Geoffrey Edward (My University, 2017)
Corporate Entrepreneurship is a familiar concept within the banking industry in South Africa and has been used successfully as a sustainable growth strategy. This concept, however, is not widely recognised within the engineering sector in South Africa which focuses more on a product and production approach to marketing rather than being customer centric, innovative and entrepreneurial. The mining sector has additionally been subjected to myriad economic factors, including fluctuating commodity prices and volatile exchange rates with a significant portion of the engineering sector servicing the mining industry. Competition within the industries is becoming fierce as businesses compete on pricing locally and face threats from Eastern countries entering the South African market. The adoption of an entrepreneurial culture within organisations has been implemented with great success by other sectors, locally and internationally, and has been linked to the continued profitability and success of organisations that implement entrepreneurship as a strategic driver. This research examines whether corporate entrepreneurship exists through the various dimensions of entrepreneurial orientation and entrepreneurial intensity. Data were collected from nine respondents in the form of semi-structured, face-to-face interviews with senior management in eight different industries in the engineering sector. Purposive sampling was used to identify the participants and a thematic analysis was conducted on the data garnered through the interview process. The key findings revealed that the engineering sector in South Africa has varying dimensions of entrepreneurial orientation and these are presented in a multitude of combinations with varying degrees of entrepreneurial intensity.
MBA(Thesis)
Keywords: Entrepreneurship -- South Africa.Organizational change -- South Africa.Engineering firms -- South Africa.